Pebax/MWCNTs‐NH2 mixed matrix membranes for enhanced CO2/N2 separation. Issue 2 (16th March 2020) - Song, Chunfeng; Mujahid, Muhammad; Li, Run; Ahmad, Siraj; Liu, Qingling; Zhang, Bing; Kitamura, Yutaka
Abstract: Mixed matrix membranes (MMMs) played a promising role in gas separation. However, the trade‐off between permeability and selectivity is still a challenge for its commercial application. Rational design of the inorganic filler, compatibility of filler with the polymer, and dispersion of filler into the polymer have a significant influence on the morphology and separation performance of a membrane. In this study, in order to produce defect‐free flat sheet MMMs, two different solvents (N‐methyl‐2‐pyrrolidone and ethanol/water) were investigated to maximize the dispersion of filler (multi‐walled carbon nanotubes, MWCNTs) in Pebax. The prepared membranes were characterized by scanning electron microscope (SEM), Fourier‐transform infrared spectroscopy (FTIR), and X‐ray diffraction (XRD) analysis. CO2 /N2 permeation tests were undertaken to investigate the solvent effect on membrane permeation properties. The result showed that membranes fabricated with higher molar volume solvent were more efficient for CO2 separation. Considering the trade‐off between different parameters (molar volume of solvent, fraction‐free volume, crystallinity of membranes), the permeability and CO2 /N2 selectivity of Pebax/MWCNTs MMMs was optimized to 405 Barrer and 51, respectively. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.